Macrophage-derived MMP-8 determines smooth muscle cell differentiation from adventitia stem/progenitor cells and promotes neointima hyperplasia. Issue 1 (7th March 2019) - Yang, Feng; Chen, Qishan; Yang, Mei; Maguire, Eithne Margaret; Yu, Xiaotian; He, Shiping; Xiao, Rui; Wang, Claire S; An, Weiwei; Wu, Wei; Zhou, Yijiang; Xiao, Qingzhong; et al.
Abstract: Aims: Emerging evidence has suggested that adventitia stem/progenitor cells (AdSPCs) migrate into the intima of arteries in response to injury, where they differentiate towards smooth muscle cells (SMCs) and participate in neointimal hyperplasia. We have previously identified matrix metalloproteinase-8 (MMP8) as a key player in atherogenesis. In this study, we aimed to investigate the functional roles of macrophage-derived MMP8 in AdSPC differentiation and injury-induced arterial remodelling. Methods and results: We first observed an important role for MMP8 in SMC differentiation from embryonic stem cells, but this effect was not seen in AdSPCs. Instead, through macrophages/AdSPCs co-culture and macrophage conditional culture medium studies, we have demonstrated that the MMP8 protein secreted from macrophages promotes SMC differentiation from AdSPCs. Mechanistically, we showed that macrophage-derived MMP8 promotes SMC differentiation from AdSPCs through modulating transforming growth factor-β activity and a disintegrin and metalloproteinase domain-containing protein 10 (ADAM10)/Notch1 signalling. We further demonstrated that the binding site for C BF1, S uppressor of Hairless, and L ag-1 (CSL) within SMC gene promoters is responsible for Notch1 mediated SMC differentiation. Finally, we demonstrated that macrophage-derived MMP8 increased injury-induced neointimal SMC hyperplasia by activating ADAM10/Notch1 signalling. Conclusions: We have identified macrophage-derived MMP8 as a regulator in SMC differentiation from AdSPCs and neointimal SMC hyperplasia in response to injury. Our data provide new insights into the roles of MMP8 in AdSPC differentiation and the pathogenesis of neointima formation in the context of angiographic restenosis, and therefore may aid in the development of novel therapeutic agents for the prevention of this disease.